The Importance of Landscape Design in the Formation of The Architecture of the Medieval City of Khiva - M.S. Zikirov (Genius Journals, 2023)
In the article, the laws of landscape design used in the development of art in medieval Khiva (Khorazm) architecture were researched, and scientific recommendations and conclusions were given regarding its application. Also, the opinions of Khiva architecture and foreign landscape specialists about green areas in the country are given. Considerations are given about the importance of gardens in the formation of castles.
Keywords: farsakh; anchors; attraction